2007
DOI: 10.1002/adma.200602975
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance, Flexible Hydrogen Sensors That Use Carbon Nanotubes Decorated with Palladium Nanoparticles

Abstract: Single‐walled carbon nanotubes decorated with Pd nanoparticles on thin poly(ethylene terephthalate) sheets serve as building blocks for the fabrication of mechanically flexible hydrogen sensors (left frame of the figure) with excellent sensing performance. The sensitivities (i.e., the change of resistance) of the as‐fabricated sensors are comparable to (or even higher than) the sensors built on rigid substrates and the responses are reversible (right frame of the figure).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
202
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 344 publications
(206 citation statements)
references
References 69 publications
2
202
0
Order By: Relevance
“…Response times and recovery times obtained for the samples are in good agreement [17,19,20,21,23] or lower [40] than those found for similar devices in other works.…”
Section: Tests In Synthetic Airsupporting
confidence: 86%
See 2 more Smart Citations
“…Response times and recovery times obtained for the samples are in good agreement [17,19,20,21,23] or lower [40] than those found for similar devices in other works.…”
Section: Tests In Synthetic Airsupporting
confidence: 86%
“…Interestingly, the recovery of the resistance after removal of the H 2 gas, follows the same trend as the H 2 O, thus demonstrating that the recovery of the signal is related to hydrogen oxidation and water evolution. The relevance of the water formation reaction on the recuperation stage of the device has been reported in the literature [19]. .…”
Section: Role Of O 2 In the Sensor Performance And Recovery Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Kong et al demonstrated that individual SWCNTs, as well as SWCNT networks, show enhanced H 2 sensing capability after being decorated with Pd NPs (Kong et al 2001); the resistance of a single-SWCNT (semiconducting) device doubled upon exposure to 400 ppm H 2 . Sun et al fabricated flexible H 2 sensors on plastic substrates using necklace-like structures of Pd NPs electrochemically deposited on SWCNT networks (Sun & Wang 2007). MWCNTs decorated with discrete SnO 2 NPs showed room-temperature gas sensing capability for low concentration gases (H 2 , CO, and NO 2 ) diluted in air (Lu et al 2009).…”
Section: Cnt-np: a New Class Of Multifunctional Nanomaterialsmentioning
confidence: 99%
“…CNTs decorated with NPs form a new class of hybrid nanomaterials that could potentially display not only the unique properties of NPs (Fissan et al 2003;Scher et al 2003) and nanotubes (Dresselhaus et al 2001;de Heer 2004;), but also additional novel physical and chemical properties due to the interaction between CNTs and attached NPs. These hybrid nanomaterials have recently been shown as promising building blocks for various applications, including gas sensors (Kong et al 2001;Sun & Wang 2007;Lu et al 2009), fuel cells (Mu et al 2005;Kongkanand et al 2006;Robel et al 2006), solar cells (Landi et al 2005;Guldi et al 2006;Kongkanand et al 2007; Lee et al 2007), Li-ion batteries (Zhang et al 2006), hydrogen storage Anson et al 2006), and transparent conductive electrodes (Kong et al 2007). This chapter begins by outlining the significance of CNT-NP hybrid structures in terms of materials advantages and potential applications.…”
Section: Introductionmentioning
confidence: 99%